Conformation control of triplet state diffusion in platinum containing polyfluorene copolymers. Issue 1 (4th September 2022) - Lambeva, Nikol T.; Mullen, Claudius C.; Gao, Xuyu; Wu, Qingjing; Taylor, Robert A.; Tao, Youtian; Bradley, Donal D. C.
Abstract: The spectral diffusion of singlet and triplet excitons in 9, 9‐dioctylfluorene‐based conjugated copolymers is investigated using photoluminescence spectroscopy at both low (5 K) and room temperature (300 K). Inclusion of a N, N ‐diphenyl‐4‐(pyridin‐2‐yl)aniline moiety into the polymer backbone allows subsequent cyclometalation with platinum acetylacetonate to increase the spin‐orbit coupling and yield radiative decay from the triplet state. For suitably low fractions (≤5%) of bulky ligand inclusion, cyclometalated or not, the resulting longer sequences of fluorene units are able to adopt the chain‐extended β‐ phase conformation. Comparison between the phosphorescence spectral diffusion in glassy‐ and β‐ phase Pt‐copolymer samples provide insight into the triplet exciton transfer in more‐ or less‐disordered conjugated polymer films. It is found in the glassy‐phase samples with shorter conjugation lengths that the triplet exciton relaxation becomes frustrated at low temperature due to a freezing out of the thermally activated hops required to move from one conjugated segment to another. In contrast, for films containing β‐ phase chain segments, with increased conjugation lengths, this frustration is lifted as more hopping sites remain accessible through intra‐segment motion. This work demonstrates controlled use of changes in molecular conformation to optimize triplet diffusion properties in a member of the widely deployed fluorene‐based conjugated copolymers. Abstract :